MEASURING AND ANALYZING THE IMPACT OF GOVERNMENT SPENDING ON SOME ECONOMIC VARIABLES IN IRAQ FOR THE PERIOD 2004-2020 - Assist. Prof. Dr. Azhar Shamran Jabur (Scholar Express Journals, 2024)
Government spending is one of the basic and important elements in influencing economic variables and is one of the tools of fiscal policy for government intervention in economic life in order to achieve economic and social goals set by the Iraqi government. This study specializes in measuring and analyzing the impact of government spending on some economic variables in the Iraq for the period 2004-2020. This is done through a standard model of the data used, represented by (government spending, gross domestic product, unemployment rate and inflation rate). Government spending is the main and effective element in influencing the various economic variables in the country. Since the Iraqi economy is a rentier economy that depends heavily on the oil sector for its revenues due to the weak contribution of other sectors to government revenues and in the formation of GDP. As a result, the government spending has a significant impact on some of the economic variables under study, and the study has found that government spending has a significant impact on the economic variables, represented by GDP, inflation rate, unemployment rate according to the premise of economic theory and as a result of those results that we have reached, so we recommend that the Iraqi government should adopt modern methods and methods to rationalize government spending according to the revenues of the Iraqi government. As well as providing the appropriate infrastructure in order to overcome all the problems and obstacles facing the economic variables under discussion in order to achieve the desired goals by the government and achieve economic growth in the country
Keywords: Government; GDP; Economic Growth